The Influence of Hospital Volume on Circumferential Resection Margin Involvement: Results of the Dutch Surgical Colorectal Audit. Issue 4 (April 2016) - Gietelink, Lieke; Henneman, Daniel; van Leersum, Nicoline J.; de Noo, Mirre; Manusama, Eric; Tanis, Pieter J.; Tollenaar, Rob A. E. M.; Wouters, Michel W. J. M.
Abstract : This population-based study evaluates the association between hospital volume and CRM (circumferential resection margin) involvement, adjusted for other confounders, in rectal cancer surgery. A low hospital volume (<20 cases/year) was independently associated with a higher risk of CRM involvement (odds ratio = 1.54; 95% CI: 1.12–2.11).